The Influence of Near Vision Tasks on Intraocular Pressure in Normal Subjects and Glaucoma Patients - Mohammad Pakravan; Azadeh Samaeili; Hamed Esfandiari; Kiana Hassanpour; Sadid Hooshmandi; Shahin Yazdani; Farideh Sharifipour; Azadeh Doozandeh; Bahram Einollahi; Parastou Pakravan; Mohammad Hasan Shahriari; Bahareh Kheiri (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To investigate the effect of static accommodative tasks on intraocular pressure (IOP) of glaucomatous and normal eyes. Methods: Four groups of subjects categorized as primary open-angle glaucoma (POAG), primary angle-closure suspects (PACS), normal age-matched controls, and normal young adults (NYA; age < 40 years) were enrolled. The baseline IOPs were measured after the subjects were looking at a distant target for 15 min. Static accommodation was obtained by execution of near vision tasks (reading at 33 cm in daylight [300 lux] for 60 min). IOPs were measured at 15, 30, 45, and 60 min intervals while accommodating and then measured again after 15 min of relaxing accommodation while looking at a distant target. Results: One-hundred and eighteen eyes of 98 subjects were recruited. The study groups consisted of the following categories: 25 POAG (46 eyes), 24 PACS (47 eyes), 25 matched controls (50 eyes), and 24 NYA (48 eyes). Within all groups, the mean IOP decreased throughout the accommodation period at all time points. Maximum IOP reduction after accommodation was detected at the 30-min time among the POAG subjects, at the 45-min time in the PACS and matched control groups, and at 15 min after the relaxation of accommodation in the NYA group. IOP reduction levels showed no statistically significant difference among POAG, PACS, and the normal matched groups in their response to accommodation. However, NYA had significantly lower IOP and greater IOP reduction after the resting period (relaxation of accommodation). Conclusion: Static accommodative tasks can significantly reduce IOP in normal, POAG, and PACS individuals. Encouraging glaucoma patients to practice periodical near vision tasks could be viewed as an adjunctive measure for glaucoma management.